Nuzulul quran: Makna dan hikmahnya bagi umat Islam - Elsanti, Nova Sevila; Aman, Moh Muhibbul; Rahmadina, Sintia Fa'iz (Maliki Interdisciplinary Journal, 2025)
This study will discuss the concept of Nuzrul Quran, namely the process of the revelation of the Qur'an to the Prophet Muhammad SAW. The discussion begins with an understanding of Nuzrul Quran which is clearly explained as the revelation of Allah conveyed to the Prophet Muhammad SAW through the angel Gabriel. This study also explains the differences between three terms in the Qur'an, namely Nazara, Nazara, and Anzarah. These three things have different meanings that are directly and gradually related to the process of the revelation of the Qur'an. In addition, this study also explains the wisdom of the gradual revelation of the Qur'an as follows: Strengthening the prophet's mind, weakening enemies who deny, facilitating memorization and understanding, and considering the needs of society in the context of gradually forming world law. This wisdom also strengthens the belief that the Qur'an is always the true and correct revelation of Allah. Nuzrul Quran is not only a historical event, but also has theological and educational value in building a just society, morality, and legal system. This study provides an in-depth understanding of the role of the Qur'an as a guide to life for Muslims and the main source of law to guide society towards justice, equality, and a better life